Continuité, ruptures et dissolution du quotidien : une lecture d’"Une ville en temps de guerre" d’Abdelkader Djemaï - Celdran, Hélène (2025)
In Une Ville en temps de guerre [A City in Times of War] (2013), the Algerian writer Abdelkader Djemai closely relates, through the eyes of a young adolescent, the events that occurred in Oran at the end of the Algerian War of Independence in 1961 and 1962. The article proposes an analysis of the literary devices implemented by the writer to represent everyday life in the city and its disintegration in the face of the intervention of history into the lives of its inhabitants. Initially, the analysis focuses on the everyday world of “Lahouari, a young teenager” – a world which evolves from a reassuring framework of continuity to a world of ruptures caused by the war. Later, through the recognition of a series of prolepses, the study of the temporal anchoring of the narrative shows the difficulty of recounting everyday life that is constantly threatened by the memory of wartime events. Finally, the examination of the metaphorical system of the story based on the imagery of the body and the edible shows how everyday life itself becomes an element in descripting its own disappearance. Between history and memory, everyday life is at the centre of the writer’s literary project, which he keeps alive despite its dissolution.
Keywords: Djemaï, Abdelkader